Students' Anxiety in Speaking Class and Ways of Minimising It - Ni Nyoman Padmadewi (Universitas Negeri Malang, 2016)
This study investigated the anxiety levels of ability groups streaming by yheir perceived ability. It also dealt with the investigation of possible factors which provoked the students' anxiety and finding out ways of minimizing the anxiety level. The study spproached the first problrm by conducting a survey study and the second and the third ones by a case study of two sample students. The results of the data collection showed that both groups, average and above average students felt anxious when they had speaking class. The results of the case study stated that factors like examination, individual presentation, spontaneous activity and limited availability of time were found to be the sources of students' anxiety. Conclusions and comment at the end of students' presentation, a tolerant teacher, and close relationship between the teacher and students in class were believed to help minimize students' anxiety level